Calcium alginate entrapment of Aspergillus nidulans IMPP-0785 laccase for enhanced enzyme catalytic ability, thermost ability and dye-decolorization (Bangladesh Journal of Botany, 2018)
Production of laccase using a solid-state culture of Aspergillus nidulans IMPP-0785 was optimized using barley bran. Aspergillus nidulans IMPP-0785 laccase optimum activity was observed with filtrate (29.15 U/g) as compared to supernatant and unfiltered. Free laccase and supernatant gave best results at 30.24 and 25.95 U/g, respectively for 20 min incubation time. The entrapped spores of A. nidulans IMPP-0785 showed maximal activity (16.12 U/g) at incubation time for 60 min. Immobilized laccase resulted optimal activity (29.24 U/g) for 25 min of incubation. Enzyme showed higher thermo stability of 34.28 U/g when incubated for 35 min.